An efficient method to prepare a new class of regioregular graft copolymer via a click chemistry approach1. Issue 90 (2nd October 2015) - Mane, Shivshankar R.; Sarkar, Santu; N., Vijayakameswara Rao; Sathyan, Ashlin; Shunmugam, Raja
<x xml:space="preserve">Abstract</x> Herein, we report the synthesis of a novel regioregular poly-norbornene anhydride-g-(3-hexyl thiophene) (PNBA-g-PHT) graft copolymer.